2019
DOI: 10.1590/s1678-9946201961070
|View full text |Cite
|
Sign up to set email alerts
|

Students’ HPV vaccination rates are associated with demographics, sexuality, and source of advice but not level of study in medical school

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
(28 reference statements)
1
14
1
4
Order By: Relevance
“…The average age of first sexual intercourse in participating students is similar to published data from Italian 10 , Spanish 11 and to that of female students in a Swiss study, but lower than for male students from the same study 12 . The number of respondents who have started sexual relationships in our study was similar to Brazilian medical students 13 but lower than in Spanish and Swiss students 11,14 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The average age of first sexual intercourse in participating students is similar to published data from Italian 10 , Spanish 11 and to that of female students in a Swiss study, but lower than for male students from the same study 12 . The number of respondents who have started sexual relationships in our study was similar to Brazilian medical students 13 but lower than in Spanish and Swiss students 11,14 …”
Section: Discussionsupporting
confidence: 85%
“…However, other limiting factors were also reported in different countries: concerns about the safety of the HPV vaccine and its potential side-effects, insufficient information and knowledge to make an informed decision, feeling safe from the infection, low efficacy of the vaccine and parental concerns have all been mitigating factors in the global vaccine uptake. 13,14,20 Some parents were also concerned that vaccination would encourage their children to become sexually active, as the children would believe that they were protected from contracting sexually transmitted infections. 20 However, there is no evidence that vaccination again HPV leads to increased promiscuity or unsafe sexual practices.…”
Section: Discussionmentioning
confidence: 99%
“…While the frequency of vaccination was found to be 4.5% in our study, it was reported as 5.3% in a study conducted with sixth grade students in the Faculty of Medicine at Hacettepe University, (Turkey) [16]. In the literature, this rate is given as 21.1% to 32.1% among medical faculty students in Brazil and the USA, respectively [17,18]. We know that as of 2017, 71 countries in the world have included the HPV vaccine for girls in the government's routine vaccination program 19], and the vaccine is free in the USA and most European countries.…”
Section: Discussioncontrasting
confidence: 48%
“…[ 14 ] Similar vaccination acceptance rate of 6% and 10% was observed in two different medical colleges of India and slightly higher rate of 21.1% in a Brazilian study. [ 22 23 ] The willingness to accept vaccine was 66.8% in a study by Mehta et al . and 64% by Kamini et al .…”
Section: Discussionmentioning
confidence: 99%